Penerapan Metode Mind Mapping Untuk Meningkatkan Pemahaman Peserta Didik dalam Pembelajaran Pendidikan Agama Kristen di Kelas VIII-3 SMP Negeri 4 Pineleng - Jessica Pangkey; Deflita Lumi; Horasman Pardemunta Munthe (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study was motivated by the low level of understanding among students in Christian Religious Education classes in Grade 8-3 at SMP Negeri 4 Pineleng. The pre-cycle results showed an average class score of 49.33 with a learning achievement rate of 13.33%, meaning that only 2 out of 15 students met the minimum passing score. The objective of this study was to improve students’ understanding through the application of the Mind Mapping method. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted over two cycles. The research subjects consisted of 15 students in Class VIII-3 at SMP Negeri 4 Pineleng for the 2025/2026 academic year. Data collection techniques included observation, testing, and documentation. The results of the study indicate that the application of the Mind Mapping method can improve students’ understanding. The average class score increased from 49.33 in the pre-cycle to 78.33 in Cycle I with a mastery rate of 73.33%, and increased further to 92.67 in Cycle II with a mastery rate of 100%. Student and teacher engagement also improved in each cycle. Thus, the Mind Mapping method is effective for improving students’ understanding of the “Me and My Service” material in Christian Religious Education instruction in Grade 8-3 at SMP Negeri 4 Pineleng. Based on these findings, it is recommended that the Mind Mapping method be used as an alternative teaching method in Christian Religious Education to enhance students’ understanding, engagement, and creativity.